Evaluation of Platelet Count and Indices for Diagnosing Neonatal Sepsis: A Cross-Sectional Analysis - Mullaivendan G, A. Sujithkumar (Journal of Neonatal Surgery, 2025)
Introduction Neonatal sepsis remains a leading cause of morbidity and mortality in neonates worldwide. Early and accurate diagnosis is crucial for timely intervention. Platelet parameters, such as platelet count, Mean Platelet Volume (MPV), and Platelet Distribution Width (PDW), have emerged as potential biomarkers for the early identification of neonatal sepsis. This study aims to evaluate the role of platelet indices in diagnosing neonatal sepsis. Materials & Methods A cross-sectional observational study was conducted in a tertiary care Neonatal Intensive Care Unit (NICU) from June 2023 to December 2024. A total of 100 neonates suspected of sepsis were enrolled. Neonates were categorized into two groups: confirmed sepsis (culture-positive) and probable sepsis (culture-negative). Platelet count, MPV, and PDW were measured on admission, day 3, and day 7. Blood cultures were processed using the BACTEC automated system. Statistical analysis was performed using SPSS version 23.0. Results Among the 100 neonates, 28 had culture-positive sepsis, and 72 had culture-negative sepsis. Platelet counts were significantly lower in culture-positive neonates at all time points (p < 0.05). MPV was significantly higher in culture-positive neonates compared to culture-negative ones (p < 0.05). However, PDW showed no statistically significant differences between the two groups. Escherichia coli was the most common organism isolated in blood cultures (64.3%). Conclusion This study highlights the potential of platelet count and MPV as early, cost-effective biomarkers for diagnosing neonatal sepsis. While PDW did not show significant diagnostic value, platelet count and MPV could serve as useful adjuncts to clinical assessment, particularly in resource-limited settings. Further multicenter studies are needed to validate these findings.